2018
DOI: 10.1177/1358863x17751656
|View full text |Cite
|
Sign up to set email alerts
|

Simulation for competency assessment in vascular and cardiac ultrasound

Abstract: Healthcare providers who use peripheral vascular and cardiac ultrasound require specialized training to develop the technical and interpretive skills necessary to perform accurate diagnostic tests. Assessment of competence is a critical component of training that documents a learner's progress and is a requirement for competency-based medical education (CBME) as well as specialty certification or credentialing. The use of simulation for CBME in diagnostic ultrasound is particularly appealing since it incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
(51 reference statements)
0
10
0
1
Order By: Relevance
“…This makes it possible to assess the accuracy of the measurements and the skill of the examiner, as well as to identify sources of error. 5 Review of images from the volume flow measurements made by examiner 2 in this study indicated a specific source of error involving scanning technique with improper placement of the Doppler sample volume.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This makes it possible to assess the accuracy of the measurements and the skill of the examiner, as well as to identify sources of error. 5 Review of images from the volume flow measurements made by examiner 2 in this study indicated a specific source of error involving scanning technique with improper placement of the Doppler sample volume.…”
Section: Discussionmentioning
confidence: 74%
“…Simulators are assuming a more prominent role in medical settings for both procedural training and assessment of psychomotor skills. 5,8 Duplex scanners are the primary instrumentation for vascular ultrasound, but simulating the Doppler component of duplex scanning presents unique technical challenges. The duplex ultrasound simulator we developed at the University of Washington uses 3D models of vessel geometry and computational fluid dynamics modeling to provide a realistic representation of arterial flow displayed as Doppler spectral waveforms and color-flow images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey attracted more respondents from private practices and vascular speciality practices than from the reported national average (Table 1). This is likely due to AVF scanning being considered as complex and requiring a high degree of specialised vascular skill 8,13 …”
Section: Discussionmentioning
confidence: 99%
“…Standardization can be obtained by implementation of simulation training sessions. 15 Training is also an important tool to document the patency of venous lines. In a multidisciplinary team care model, relaying information between professional taking care of patients is a powerful tool to reduce adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%